Speech text of cheque presentation ceremony: awarding of education fund by Yayasan Arshad Ayub to the Faculty of Accountancy, UiTM / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
My heartiest congratulations to the Faculty of Accountancy which will receive a total of Two Hundred Thousand Ringgit Malaysia education fund sponsorship awarded by Yayasan Arshad Ayub today.